Reproducibility of the Time of Intraocular Pressure Peaks During Water-drinking Test in Patients Treated for Open-angle Glaucoma - Carolina TN Susanna; C. Gustavo De Moraes; Paula Alhadeff; Bianca TN Susanna; Fernanda TN Susanna; Renato Antunes Schiave Germano; Remo Susanna Jr (Journal of Ophthalmic & Vision Research)
Purpose: To evaluate the reproducibility and between-eyes symmetry of time of the intraocular pressure (IOP) elicited with the water drinking test (WDT) in treated glaucomatous patients. Methods: Prospective cohort study that included ninety-nine patients, 198 eyes of treated primary open-angle glaucoma patients.  All patients underwent the WDT performed in two consecutive visits without any change in the therapeutic regimen. The interval between tests was 4 to 6 months. The test was performed at the same time of the day (4.00PM +/- one hour). The reproducibility of time of the IOP peak and the relationship between peak times between fellow eyes during the two consecutive WDT sessions were assessed. Results: 59.6% and 71% of IOP peaks occurred at the same time during the two WDT sessions in right and left eyes, respectively. In the first and second WDT sessions, the agreement in IOP peak times between eyes was 60% and 63%, respectively. Conclusion: There was modest reproducibility in the time of IOP peaks between two consecutive WDT sessions, as well as moderate agreement in the time of peaks between fellow eyes. In light of these findings, clinicians should avoid performing simplified versions of the WDT to evaluate IOP peaks.